Co‐Template Directed Synthesis of Gold Nanoparticles in Mesoporous Titanium Dioxide. Issue 38 (10th June 2018) - Liu, Ben; Louis, Michael; Jin, Lei; Li, Gonghu; He, Jie
Abstract: A bottom‐up synthetic methodology to encapsulate pre‐synthesized, well‐defined gold nanoparticles (AuNPs) into mesoporous titanium dioxide framework (Au@ m TiO2 ) is reported. This method employs two structurally and chemically similar templates of amphiphilic block copolymers as well as poly(ethylene oxide)‐tethered AuNPs, which showed excellent stability during sol–gel transition and thermal annealing at elevated temperatures. Such synthesis enabled precise control of sizes and loading of AuNPs within the mesoporous TiO2 framework. In light‐driven methanol dehydrogenation, the presence of AuNPs significantly enhanced the photocatalytic activity of m TiO2 . This co‐template‐directed synthesis presents new opportunities to understand the effect of AuNP size in photocatalysis using Au@ m TiO2 materials. Abstract : Attach the block : The use of two structurally and chemically similar templates of amphiphilic block copolymers as well as poly(ethylene oxide)‐tethered AuNPs enabled precise control of sizes and loading of Au nanoparticles within a mesoporous TiO2 framework.